ANALISIS BENTUK SOAL TEMA DIE ZAHLEN PADA APLIKASI DEUTSCHTRAINER A1 BAHASA JERMAN KELAS X SEMESTER I - Indriani, Tiara; Julaikah, Dwi Imroatu (LATERNE, 2022)
Exercise is an activity in the learning process that aims to motivate students to better understand the subject matter in order to get better results. In today's digital era, there are lots of media that students can use to practice working on German questions, one of which is the Deutschtrainer A1 application. There is one theme of die Zahlen die that will be analyzed in this article. The formulation of the problem in this article is whether the practice questions on the die Zahlen theme in the Deutschtrainer A1 application are in accordance with the 2013 curriculum and the cognitive level of the questions. The purpose of this article is to describe the suitability of the die Zahlen practice questions with the 2013 curriculum and the cognitive level of the questions. The method used is a descriptive qualitative method with a literature study technique. The data in this article are 20 practice questions with the die Zahlen theme. The data source is obtained from the Deutschtrainer A1 Application. The analytical technique used in this article is Grounded theory Barney G. Glaser and Anselm L. Strauss. The benefit of writing this article is that it can determine the suitability of the practice on the theme of die Zahlen with the 2013 curriculum and the cognitive level of the questions. The results show that the practice questions on the die Zahlen theme in the Deutschtrainer A1 application are in accordance with the 2013 curriculum and each question's cognitive level.